55.4k views
2 votes
PLEASE HURRY!simplfiy the expresstion 6x-3-9x-2

User Mornirch
by
5.1k points

2 Answers

5 votes

Answer:

-3x-5

Explanation:

Let's simplify step-by-step.

6x - 3 - 9x - 2

= 6x + -3 + -9x + -2

Combine Like Terms:

= 6x + -3 + -9x + 2

= (6x + -9x) + (-3 + -2)

= -3x + -5

= -3x-5

So therefore that is how you found your answer: -3x-5

User Raghava
by
5.1k points
5 votes

Answer: -(3 x + 5)


Simplify the following:

6 x - 9 x - 3 - 2

Grouping like terms, 6 x - 9 x - 3 - 2 = (6 x - 9 x) + (-3 - 2):

(6 x - 9 x) + (-3 - 2)

6 x - 9 x = -3 x:

-3 x + (-3 - 2)

-3 - 2 = -5:

-5 - 3 x

Factor -1 out of -3 x - 5:

Answer: -(3 x + 5)

User Hirvesh
by
5.2k points